Czynniki konkurencyjności regionów - Raszkowski, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article presents problems connected with the concept of regions' competitiveness. It attempts at defining the term "competitiveness". There are presented classifications of factors influencing competitiveness and an exemplary listing of determinants for regions' competitiveness. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 66-73